TANAM BUAH DALAM POT (TABULAMPOT) SEBAGAI PENGUATAN EKONOMI DAN SOSIAL MASYARAKATDESA CALUK, DUSUN GUPIT, KECAMATAN SLAHUNG, PONOROGO - Niswatul Hidayati (InEJ: Indonesian Engagement Journal, 2021)
ABSTRAKEkonomiadalah salah satufaktor dan unsur yang sangatpentingdalampembangunanperadabanmanusia. Jika kondisiekonomikuat dan sejahteramakaelemen-elemen yang lain dalammasyarakatakanikutkuat dan kondusif.Dalamrangkapemberdayaanekonomiitu pula pendampingandilakukanmelaluiprogram tanambuahdalam pot atautabulampotyang dipilihsebagaibentukpengabdiankepadamasyarakatdesaCaluk.KondisigeografisdesaCalukberupatanah yang tandusmenjadiasetsekaligustantangandalampendampingan kali ini. Disisi yang lain, meskipunkondisitanahnyatandusnamunmayoritasmasyarakatCalukadalahpetani. Maka, program tanambuahdalam pot menjadipilihankarenasedikitmembutuhkan air sertalahan yang tidakluas. PendekatandalampendampinganmasyarakatinimenggunakanmetodeAsset Based Community – Driven Development (ABCD) denganmenggaliasetsebagaikekuatanmasyarakatdesaCaluk. Pendampingandilakukanmulaidarimencangkoksebagaibibittanaman, membuat media tanaman, sampaitanamanberbuah dan memilikinilaiekonomisehinggabisadijual.Kata kunci: peningkatanekonomi, tanambuahdalam pot, aset. ABSTRACTEconomy is one of important factor and elements in developing human civilization. If the economy is stable and strong, then other element of life of the community will be strong and conducive. One of the way to develop the economy of a community is by giving them guidance or mentoring how to grow plant using a pot. The mentoring is chosen as the devotion form to the society especially in Caluk village. In one side, the majority of the lands in Caluk village are barren which is considered not only as a challenge but also as an asset. In another side, most of people in Caluk village are farmer. Therefore, growing plant in a pot is a practical one because it does not need a vast area. This mentoring will be conducted by using ABCD (Asset Based Community – Driven Development) approach. This approach will stress on digging the asset of community as the main power. This mentoring will begin with grafting as a method to gain seed, then making the plant media, until the plant bare its fruit and ready to sell.  Keywords: economic development, growing plant in a pot, asset.